Sex and External Size Specific Limitations in Assessing Bone Health From Adult Hand Radiographs. (29th June 2022) - Bigelow, Erin M.R.; Goulet, Robert W.; Ciarelli, Antonio; Schlecht, Stephen H.; Kohn, David H.; Bredbenner, Todd L.; Harlow, Sioban D.; Karvonen‐Gutierrez, Carrie A.; Jepsen, Karl J.
ABSTRACT: Morphological parameters measured for the second metacarpal from hand radiographs are used clinically for assessing bone health during growth and aging. Understanding how these morphological parameters relate to metacarpal strength and strength at other anatomical sites is critical for providing informed decision‐making regarding treatment strategies and effectiveness. The goals of this study were to evaluate the extent to which 11 morphological parameters, nine of which were measured from hand radiographs, relate to experimentally measured whole‐bone strength assessed at multiple anatomical sites and to test whether these associations differed between men and women. Bone morphology and strength were assessed for the second and third metacarpals, radial diaphysis, femoral diaphysis, and proximal femur for 28 white male donors (18–89 years old) and 35 white female donors (36–89+ years old). The only morphological parameter to show a significant correlation with strength without a sex‐specific effect was cortical area. Dimensionless morphological parameters derived from hand radiographs correlated significantly with strength for females, but few did for males. Males and females showed a significant association between the circularity of the metacarpal cross‐section and the outer width measured in the mediolateral direction. This cross‐sectional shape variation contributed to systematic bias in estimating strength using cortical area and assuming a circular cross‐section. This was confirmed by the observation that use of elliptical formulas reduced the systematic bias associated with using circular approximations for morphology. Thus, cortical area was the best predictor of strength without a sex‐specific difference in the correlation but was not without limitations owing to out‐of‐plane shape variations. The dependence of cross‐sectional shape on the outer bone width measured from a hand radiograph may provide a way to further improve bone health assessments and informed decision making for optimizing strength‐building and fracture‐prevention treatment strategies. © 2022 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.